Exposure to airborne particles associated with the handling of graphene nanoplatelets - Spinazzè, Andrea; Cattaneo, Andrea; Borghi, Francesca; Del Buono, Luca; Campagnolo, Davide; Rovelli, Sabrina; Cavallo, Domenico Maria (La Medicina del Lavoro, 2018)
Background: It is recognized that engineering control measures are needed to reduce occupational exposure to engineered nanomaterials (NMs): of these, fume hoods are among the most widespread collective protection equipment used while handling NMs in occupational settings.  It is known that in some circumstances, handling NMs in fume hoods can result in a significant release of NMs. Objective: To assess the effectiveness of fume hoods in reducing exposure while handling graphene nanoplatelets and to define the conditions that result in a lower dispersion of particles and thus less operator exposure. Methods: An experimental protocol was established to monitor the variations of airborne particle concentrations while handling graphene in fume hoods (transferring and pouring). The measurement locations were at the laboratory, inside the hood and at operator’s breathing zone. Handling tasks were performed under different operating conditions: the variable factors included hood face velocity and sash height. Results: Results of this study indicate that the handling of graphene nanoplatelets may pose a potential risk of contamination of the work environment and hence exposure of the involved operators, if adequate control measures are not taken. In fact, when inadequate or not sufficiently cautionary operational conditions were utilized, non-negligible increases in airborne graphene particle concentrations during the nanomaterial manipulation phases were observed. Conclusions: Some operating conditions (e.g., face velocity, sash height) can be adjusted to avoid relevant personal exposure conditions and contamination of the work environment by NMs, thus ensuring safer conditions.